2019
DOI: 10.31025/2611-4135/2019.13871
|View full text |Cite
|
Sign up to set email alerts
|

Production and Characterisation of SRF Premium Quality From Municipal and Commercial Solid Non-Hazardous Wastes in Austria, Croatia, Slovenia and Slovakia

Abstract: The production of Solid Recovered Fuel (SRF) and related energy recovery in the European cement industry represents the state of the art in waste management, having evolved into a highly important part of a sustainable and circular economy. This paper describes the production and quality of eight Solid Recovered Fuels (SRF) of PREMIUM quality that are produced from Municipal (Mixed) and selected Commercial Wastes (i.e. Bulky and Lightweight Fraction from Plastic Sorting Plants) in three types of treatment plan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 12 publications
1
8
0
1
Order By: Relevance
“…This development is probably in accordance with the development of municipal waste management performance (i.e. increasing of recycling rates for municipal waste over last years), discussed by Pomberger et al (2017) and Sarc et al (submitted). The proportion of fraction ‘Paper, cardboard and cardboard packaging’ is still in the same range (i.e.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…This development is probably in accordance with the development of municipal waste management performance (i.e. increasing of recycling rates for municipal waste over last years), discussed by Pomberger et al (2017) and Sarc et al (submitted). The proportion of fraction ‘Paper, cardboard and cardboard packaging’ is still in the same range (i.e.…”
Section: Discussionsupporting
confidence: 76%
“…All (9) SRF MEDIUM Quality are produced in Austrian waste treatment plants while SRF PREMIUM Quality is produced in Austria (6), Croatia (3), Slovenia (1) and Slovakia (1). Selected results on SRF PREMIUM Quality produced in Croatia are given by Sarc et al (2018) and SRF PREMIUM Quality produced in all four countries by Sarc et al (submitted).…”
Section: Update 2019 – Case Study: Utilisation Of Srf Premium Quality and Srf Medium Quality In A Cement Kilnmentioning
confidence: 99%
“…Furthermore, the standard requires certain chemical elements and properties to be determined for the specification of SRF. Sarc et al (2014Sarc et al ( , 2019Sarc et al ( , 2020 extensively reported on the chemical-physical quality of SRF from mixed municipal and commercial waste for its energy recovery in cement industry. When utilizing SRF in Austrian cement industry, input limits exist for delivered (unburnt) waste.…”
Section: The Use Of Srfs In the Austrian Cement Industrymentioning
confidence: 99%
“…Mechanical multistage processing is a technical pre-condition for production of quality assured SRF. As shown by Sarc et al (2014Sarc et al ( , 2019Sarc et al ( , 2020, there are various plant types and technical concepts applied in different regions and countries in the EU. Next, different processing steps and their extent and intensity are required to treat the various types and qualities of input waste.…”
Section: Mechanical Multistage Processing For Combined Production Of ...mentioning
confidence: 99%
“…Other works were published on this topic, however, none clearly determines such parameters for the producer gas made out of SRF gasification. Thus, determination of these parameters will be very important in near future, especially while SRF material represents quite a diverse mixture of materials [11], [12].…”
Section: Introductionmentioning
confidence: 99%